Delta Neutrophil Index in Coronary Artery Bypass Surgery: An Innovation in Postoperative Mortality Assessment - Bilgiç A; Toprak B; Kaya H (Journal of Inflammation Research)
Abdulkadir Bilgiç,1 Burak Toprak,2 Hamide Kaya3 1Department of Cardiovascular Surgery, Mersin University Faculty of Medicine Hospital, Mersin, Turkey; 2Department of Cardiovascular Surgery, Mersin City Education and Research Hospital, Mersin, Turkey; 3Department of Microbiology, Mersin University Faculty of Medicine Hospital, Mersin, TurkeyCorrespondence: Burak Toprak, Department of Cardiovascular Surgery, Mersin City Education and Research Hospital, Kuzeykent District, 31131 Street No: 1, Floor: 6, Flat No: 11, Yenişehir, Mersin, 33120, Turkey, Email brk.tprk@gmail.comBackground: Recent interest has focused on the role of inflammatory markers in assessing coronary artery disease (CAD) severity, especially in the early stages. However, there remains a gap in identifying reliable biomarkers to predict postoperative mortality in patients undergoing coronary artery bypass grafting (CABG). Traditional markers such as C-reactive protein (CRP) and white blood cell (WBC) counts are commonly used but have limitations in specificity and prognostic value. The Delta Neutrophil Index (DNI), which reflects immature granulocyte levels, offers a promising alternative. Unlike CRP and WBC, DNI specifically measures the acute inflammatory response, providing a more targeted indicator of risk. This study evaluates the significance of postoperative DNI as a prognostic marker for early mortality in CABG patients, addressing the need for more accurate biomarkers in postoperative care.Aim: The aim of this study is to determine the significance of the Delta Neutrophil Index (DNI), which reflects the proportion of immature granulocytes, as a prognostic marker for early postoperative mortality in patients undergoing coronary artery bypass grafting (CABG).Methods: This rigorously designed retrospective cohort study was conducted at a high-volume tertiary care center specializing in cardiovascular surgery, including a robust patient cohort to ensure comprehensive data analysis and reliable conclusions. The study included a consecutive series of 446 patients who underwent coronary artery bypass grafting (CABG) between January 1, 2022, and August 1, 2023.Results: Mortality was found to be associated with preoperative DNI (p< 0.05). A 1-unit increase in pre-DNI measurement was associated with a 2.61-fold (95% Confidence Interval: 1.54– 4.45) increase in the risk of death. Additionally, mortality was also associated with postoperative DNI (p< 0.05). A 1-unit increase in postoperative DNI measurement was associated with a 10.21-fold (95% Confidence Interval: 5.08– 20.05) increase in the risk of death.Conclusion: Elevated DNI values are strong independent predictors of postoperative mortality, underscoring its critical role in perioperative risk assessment for CABG patients. Both preoperative and postoperative DNI levels are significantly linked to mortality, emphasizing DNI’s value in improving patient outcomes and reducing complications. Integrating DNI into routine clinical practice can provide a more personalized approach to care, enhancing survival and optimizing postoperative management.Keywords: delta neutrophil index, coronary artery bypass grafting, postoperative mortality, inflammatory markers